Identifying Anti-Oxidant Biosynthesis Genes in Pearl Millet [Pennisetum glaucum (L.) R. Br.] Using Genome—Wide Association Analysis - Yadav, Chandra Bhan; Tokas, Jayanti; Yadav, Devvart; Winters, Ana; Singh, Ram B.; Yadav, Rama; Gangashetty, Prakash I.; Srivastava, Rakesh K.; Yadav, Rattan S. (Frontiers in Plant Science, 2021)
Pearl millet (Pennisetum glaucum (L.) R Br.) is an important staple food crop in the semi-arid tropics of Asia and Africa. It is a cereal grain that has the prospect to be used as a substitute for wheat flour for celiac patients. It is an important antioxidant food resource present with a wide range of phenolic compounds that are good sources of natural antioxidants. The present study aimed to identify the total antioxidant content of pearl millet flour and apply it to evaluate the antioxidant activity of its 222 genotypes drawn randomly from the Pearl Millet inbred Germplasm Association Panel (PMiGAP), a world diversity panel of this crop. The total phenolic content (TPC) significantly correlated with DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity (% inhibition) which ranged from 2.32 % to 112.45 % and ferric reducing antioxidant power (FRAP) activity ranging from 21.68 to 179.66 (mg Ascorbic Acid eq./100g). Genome-wide association studies (GWAS) were conducted using 222 diverse accessions and 67K SNPs distributed across all the seven pearl millet chromosomes. Approximately, 218 SNPs were found to be strongly associated with DPPH and FRAP activity at high confidence [-log (p) > 3.0 to 7.4]. Furthermore, flanking regions of significantly associated SNPs were explored for candidate genes harvesting. This identified 18 candidate genes related to antioxidant pathway genes (Flavanone 7-O-beta—glycosyltransferase, GDSL esterase/lipase, Glutathione S-transferase) residing within or near the association signal that can be selected for further functional characterization. Pattern of genetic variability and the associated genes reported in this study are useful findings which would need further validation before their utilization in molecular breeding for high antioxidant containing pearl millet cultivars.